Catalytic Hydrothermal Carbonization of Avocado Peel - Lien Thi Tran; Minh Quang Nguyen; Ha Trong Hoang; Hoang Tien Nguyen; Thu Ha Thi Vu (Journal of Chemistry)
The hydrothermal carbonization (HTC) of avocado peel was investigated by varying the reaction temperature, reaction time, and catalyst/feedstock ratio. After the HTC process, there was a drastic change in both the structure and chemical composition of the hydrochar compared to the feedstock. This modification aids hydrochar’s improved fuel characteristics, as seen by a drop in the H/C and O/C ratios, as well as an increase in fixed carbon content. The higher heating value (HHV) increased in the feedstock to a maximum value of 27.15 MJ·kg−1, corresponding to hydrochar, which is obtained at an optimized condition. Notably, the HHV and carbon content of the noncatalytic sample are only higher than those of the feedstock but lower than those of the samples surveyed. The combustion behavior and thermal characteristics of hydrochars show that the HTC of the avocado peel in the presence of FeCl3 catalyst introduces a possible direction of application in converting agro-industrial by-products into fuel.